Improving Engineering Education in Sub-Saharan Africa - Mohamedbhai, Goolam (International Higher Education, 2015)
There is a serious lack of engineering capacity in Sub-Saharan Africa and this can hamper its industrial development. This article surveys the current state of engineering education and training in Africa, identifies the challenges in achieving quality engineering education, and highlights steps to be taken for improvement.